Thyroid function and endocrine abnormalities in elderly patients with severe chronic obstructive lung disease. - Gow, S M (1987)
Serum pituitary and thyroid hormones, testosterone, and the response of pituitary hormones to thyrotrophin releasing hormone were measured in 20 inpatients (mean age 68, range 42-81 years) with severe chronic obstructive lung disease and in 15 control convalescent inpatients (mean age 73, range 57-83 years) who had normal respiratory function. No significant differences were found in total and free thyroid hormone concentrations and basal concentrations of thyrotrophin, growth hormone, and prolactin; and their increments after injection of thyrotrophin releasing hormone were similar in patients with chronic obstructive lung disease, and control patients. Three patients with chronic obstructive lung disease, however, had no thyrotrophin responses to thyrotrophin releasing hormone. In men, low testosterone concentrations were found both in patients with chronic obstructive lung disease and in controls. Luteinising hormone concentrations were higher in men with chronic obstructive lung disease (p less than 0.02), whereas concentrations of follicle stimulating hormone in the two groups were not significantly different. There was no significant correlation between arterial blood gas tensions and these hormone measurements. General effects of age and illness may be more important than direct effects of hypoxia in determining hypothalamic-pituitary function in elderly patients with chronic obstructive lung disease.